2009
DOI: 10.1017/s1368980008003479
|View full text |Cite
|
Sign up to set email alerts
|

Folate and vitamin B12status of women of reproductive age living in Hanoi City and Hai Duong Province of Vietnam

Abstract: Objectives: To assess the folate and vitamin B 12 status of a group of Vietnamese women of reproductive age and to estimate the rate of neural tube defects (NTD) based on red blood cell (RBC) folate concentrations. Design and subjects: A representative sample of non-pregnant women (15-49 years) living in Hanoi City (n 244) and Hai Duong Province (n 245). Measures: RBC folate, plasma vitamin B 12 and plasma holo-transcobalamin (holoTC), a sensitive indicator of vitamin B 12 status. Results: Mean (95 % CI) conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
3
5
0
Order By: Relevance
“…The low prevalence of folate deficiency in women in this survey is in agreement with a recent study conducted in 2006 among women living in Hanoi and Hai Phuong provinces that did not show evidence of folate and vitamin B 12 deficiencies [11]. However, approximately one third of women in our survey had a marginal folate status.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The low prevalence of folate deficiency in women in this survey is in agreement with a recent study conducted in 2006 among women living in Hanoi and Hai Phuong provinces that did not show evidence of folate and vitamin B 12 deficiencies [11]. However, approximately one third of women in our survey had a marginal folate status.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, recent intervention pilot studies showed that the prevalence of anemia ranges from 25% to 45% in schoolchildren [8], [9] and 24% in women of reproductive age [10]. In addition, the prevalence of zinc and selenium deficiencies were also reported to be very high (>50%) in rural Vietnamese children [11]. However, another study carried out in 2008 in two Vietnamese provinces of the Mekong of Delta among women of reproductive age did not show evidence of folate and vitamin B 12 deficiencies, although many women had marginal folate status [11].…”
Section: Introductionmentioning
confidence: 99%
“…Our study carried out in 2010 shows that half of these Vietnamese women have low iron stores and the same proportion a marginal folate status [10]. Another recent study among women living in Hanoi and Hai Phuong Provinces indicated that 60% had a suboptimal folate status [42]. These results support the relevance to increase their iron and folate intakes.…”
Section: Discussionsupporting
confidence: 74%
“…Vitamin B12 is a cofactor of methionine synthase in the synthesis of methionine, the precursor of the universal methyl donor S-Adenosylmethionine (SAMe), involved in different epigenomic regulatory mechanisms and especially in fetal growth [ 22 ]. In addition, vitamin B12 plays an essential role in folate metabolism and there is increasing evidence that poor maternal vitamin B12 status may increase the risk of adverse pregnancy outcomes such as neural tube defects (NTD) [ 23 , 24 ]. Considering the lack of a defined cut-off value for vitamin B12 deficiency in pregnant women, the prevalence of this condition may be overestimated due to a dilution effect in the second trimester of pregnancy.…”
Section: Discussionmentioning
confidence: 99%